ANALISIS HUKUM ATAS PENGUATAN SISTEM PRESIDENSIAL MELALUI RENCANA PERUBAHAN KELIMA UUD 1945 - Hafiz Sutrisno; Firmanto, Fakhry (Pahlawan Tuanku Tambusai University, 2025)
This study analyzes the proposed Fifth Amendment to the 1945 Constitution to strengthen the presidential system. Although four post-reform amendments have strengthened it, the system remains weak due to the president's reliance on multiparty coalitions, overlapping authority, and suboptimal checks and balances. The method used is normative legal research with a statute approach, a conceptual approach, and a comparative approach. The results reveal important substances such as strengthening presidential authority, term limits, and structuring executive-legislative relations. Comparisons with the United States emphasize the need for a clear separation of functions and a simplification of the party system. Keywords : Presidential System, 1945 Constitution, Amendments, Fifth Amendment, Legal Analysis